Bangladeshi Honey: A Possible source of beneficial Aerobic Bacteria - Hossain, Md. Abir; Saha, Sarbojoy; Chowdhury, Abhinandan (International Journal of Environment, Agriculture and Biotechnology, 2019)
Honey is known to have many health benefits and hence had been used as natural medicine for ages. Literature suggests that bioactive agents can come from the secondary metabolites produced by the bacteria present in honey.Existenceof several bacteria has been reported in European and Australian honeys. Therefore, the aim of this study was to isolate and identify the bacteria present in honeysavailable in Bangladesh. Honey samples from seven types of natural flowers and six commercial kinds of honeyof Bangladesh were tested in this study. Prevalence of bacteria in each sample was checked through serial dilution method. Then different types of bacteria were identified by culturing them on selective agars and biochemical tests. Presence of Micrococcus luteus(100%), Streptococcus (92%), Staphylococcus aureus(77%), Bacillus (23%), Lactobacillus (15%), Klebsiella (8%) and Escherichia coli(8%) were detected.The secondary metabolites of these bacteria can be extracted and checked for potential development as medicines from nature